ANALISIS TINGKAT KESEHATAN PT. BANK BRISYARIAH PERIODE 2011-2014 DENGAN MENGGUNAKAN METODE CAMEL - Ari Kristin Prasetyoningrum; Noor Ahmad Toyyib (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2016)
The rapid development of banking as well as high levels of complexity influence the performance and increase the risk of a bank. Therefore, it is important for banks to maintain the trust because of activities related to public confidence. This study aims to determine the health level of PT. Bank BRISyariah in 2011-2014 by using CAMEL.This research used quantitative descriptive analysis aims to analyze the soundness of PT. Bank BRISyariah in 2011-2014 using the CAMEL factors include capital, asset quality, management, earnings and liquidity. Data used in this study a BRISyariah Annual Report 2011 to 2014 taken from www.brisyariah.co.id. and Quarterly Financial Report Bank BRISyariah published by Bank Indonesia was taken from www.bi.go.id.Based on the analysis of the Bank’s soundness BRISyariah using CAMEL ratio in 2011-2014 can be said that in general PT. Bank BRISyariah in conditions HEALTHY, the the first rank in the CAR, PPAP, ROA, NPM, and CR; The second rank in the KAP; BOPO ranked third; and LDR in the fourth.